TEMPERATURE AND GEOMETRY ANALYSIS IN N-LAYER WIRE ARC ADDITIVE MANUFACTURING USING GMAW AND ER70S-6 FILLER - Amat, Mohammad Azwar; Sifa, Agus; Luthfi, Muhammad; Novianto, Arif; Panjaitan, Daniel Leonardo (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2025)
WAAM products produce a relatively rough and less precise final surface. Therefore, this study investigated and analyzed the geometric dimensions of the product at each layer and cycle time to achieve N-layers with the aim of obtaining a baseline operational time and achieving WAAM dimensional accuracy of less than ±1 mm deviation. The dimensional measurement method was carried out using a Dinolite photograph, 3-D scanning, and vernier caliper. The cycle time or downtime during the WAAM process was 130 minutes for TS 200 mm/min. TS 200 produced the most consistent thickness with the lowest thickness standard deviation of ±0.49 mm, the highest material efficiency with 45.7% of the material becoming product, and 54.3% of the material being wasted. The product produced by TS 200 mm/min has dimensions of 85 × 4 × 20 mm³.